Social Distance from Vulnerable Groups. Perspectives from Students from Suceava County - Elena BUJOREAN (Association of Social and Educational Innovation, 2018)
The article aims to explore the social distance of high-school students towards certain vulnerable categories (people with disabilities, those of different religions, those without income, foreigners, refugees, Romani, people infected with HIV, homosexuals), as well as identifying the manner in which these social categories are discriminated against at school and in other public places. In the context of the current study, social distance is expressed through the level of acceptance by the respondents of persons from the aforementioned categories, as neighbours, classmates and friends. Our study shows the students' reluctance to co-exist with certain categories of vulnerable persons by stigmatizing and using social exclusion (homosexuals, Romani, people infected with HIV, immigrants). These aspects draw attention to the need to fight against ethnocentric, xenophobic or homophobic attitudes in school. At the same time, the study shows that the manifestation of intolerant attitudes coincides in many cases with the posture of victim of discriminatory manifestations.